Validation of a Highly Sensitive qPCR Assay for the Detection of Plasma Cell-Free Epstein-Barr Virus DNA in Nasopharyngeal Carcinoma Diagnosis. (27th July 2020) - Anh, Vu Nguyen Quynh; Van Ba, Nguyen; Anh, Do Tram; Ung, Nguyen Dinh; Hiep, Nguyen Hoang; Ly, Vu Thi; Hang, Dinh Thi Thu; Sy, Bui Tien; Chinh, Hoang Dao; Ky, Le Minh; Phong, Vu Truong; Luu, Nguyen Kim; et al.
Quantification of plasma cell-free Epstein Barr virus DNA (cf EBV DNA) has been suggested as a promising liquid biopsy assay for screening and early detection of nasopharyngeal carcinoma (NPC). However, the diagnostic value of this assay is currently not known in the population of Vietnam, one of the countries which contributed the most to the NPC cases. Herein, we have reported a highly sensitive quantitative polymerase chain reaction (qPCR)-based assay targeting cf EBV DNA for the detection of NPC. A standard curve with linear regression, R 2 = 0.9961 (range: 25-150 000 copies/mL) and a detection limit of 25 copies/mL were obtained using an EBV standard panel provided by the Chinese University of Hong Kong. The clinical performance of this assay was assessed using plasma samples obtained from 261 Vietnamese individuals. The optimized qPCR assay detected cf EBV DNA in plasma with a sensitivity of 97.4% and a specificity of 98.2%. The absolute quantitative results of pretreatment cf EBV DNA and patient overall clinical stages were statistically correlated ( P < .05). In summary, the remarkably high sensitivity and specificity of our optimized qPCR assay strongly supports the wide use of cf EBV DNA quantification as a routine noninvasive method in early diagnosis and management of patients with NPC.